The Sharing Economy and its discontents - Suzor, Nicolas; Burgess, Jean; Light, Ben; Matamoros-Fernandez, Ariadna; Buchbach, Jacinta; Duguay, Stefanie; Goldsmith, Ben; Gray, Mary; Wikstrom, Patrik; Chen, Yujie; et al. (AoIR Selected Papers of Internet Research, 2016)
This panel brings together a series of related critiques over labor and fairness in the sharing economy. The last decade has brought a startling growth in the deployment of networked communications technologies to organize work. Mobile apps in particular are helping to restructure contractual relationships in ways that disrupt old and create new intermediaries. The logics and affordances of these digitally mediated platforms for negotiating labor agreements differ widely in the extent to which they empower their users. On the one hand, the sharing economy present the possibility of greatly reducing transaction costs and radically increasing access to shared resources and opportunities for participation in the workforce. But at the same time, the precarious labor of the ‘gig economy’ can drive down effective wages, the material protections, and real choices for the workers upon which it depends. The rapid growth of these new markets present new challenges for understanding how work is regulated, and new opportunities for imagining how it might be organized in the future. This panel begins with a mapping of the Chinese sharing economy. The first paper provides a provocative critique of the common assumption that sharing platforms necessarily weaken the formal legal protections granted to workers. It provides a new typology to systematically characterize the range of sharing economy platforms in China according to the real resources and opportunities of the participants who share their goods and labor. The next two papers zoom in to more closely study labor on sharing economy platforms, through two different methodological approaches. The second paper provides a rich ethnographic study of women task workers in South India and the US, making visible the complex relationships around the sharing economy that are otherwise obscured behind the APIs that mediate transactions. The third paper takes on this theme and makes the sharing economy platform its central object of study. This paper examines how a task working platform structures the conflicts between neoliberal ideals of frictionless markets and the precariousness that this freedom so often brings for the laborers who depend upon it. It considers how the platform shapes the presentation of work and, by encouraging the quantified self, promotes ideal workers to maximize the platform’s value. Finally, the fourth paper turns to consider the regulation and legitimization of sharing economy platforms as they disrupt established labor markets. It focuses particularly on the disconnect between political deliberative debates over fairness and consumer protection, on the one hand, and the ongoing legitimization of sharing economy markets as reflected through the everyday experiences of consumers and workers. In this context, it provokes a series of core questions around the regulation of industry and the public interest, seeking to understand in greater detail how different approaches to organizing labor become accepted and justified. All papers ultimately ask the important question about who benefits from these new markets. We highlighting both the opportunities for reconfiguring labor relations that these markets provide, and the threats to working conditions that they pose. In doing so, we seek to move beyond the dichotomy of sharing as liberation and as exploitation to consider how platforms and networks might be designed and deployed to enhance real capabilities and opportunities for human flourishing.